INTERNATIONAL CONFERENCE ON AFRICAN BIBLIOGRAPHY - Julian W. Witherell (International African Institute / Institut International Africain, 1967)
This document, a paper presented at the International Conference on African Bibliography in 1967, details the extensive bibliographic programs focused on African studies in Washington, D.C., undertaken by the Library of Congress and the African Bibliographic Center. It describes the Library of Congress's role as a preeminent collector of Africana, highlighting the establishment and work of its African Section in compiling major annotated bibliographies, guides to official publications, and lists of serials and dissertations. It also outlines the mission and output of the African Bibliographic Center, a non-profit organization specializing in rapid dissemination of current bibliographic information through its periodical and thematic series. The paper concludes that both institutions, leveraging Washington's vast research resources, provide comprehensive bibliographic coverage essential for Africanists worldwide
Bibliographic Programs on Africa in Washington, D.C. at the Library of Congress and the African Bibliographic Centre / Réalisations de Bibliographie Africaine à Washington D.C. à la Bibliothèque du Congrès et au Centre de Bibliographie Africaine
Keywords: African Bibliography; Library of Congress; African Bibliographic Center; Africana; Official Publications